2018
DOI: 10.1002/esp.4354
|View full text |Cite
|
Sign up to set email alerts
|

Sediment budget controls on foredune height: Comparing simulation model results with field data

Abstract: The form, height and volume of coastal foredunes reflects the long‐term interaction of a suite of nearshore and aeolian processes that control the amount of sand delivered to the foredune from the beach versus the amount removed or carried inland. In this paper, the morphological evolution of more than six decades is used to inform the development of a simple computer model that simulates foredune growth. The suggestion by others that increased steepness of the seaward slope will retard sediment supply from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
91
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 83 publications
12
91
1
1
Order By: Relevance
“…Storms are most often considered erosional events to dunes, but results here and from other studies (e.g. Hesp et al ., ; Davidson‐Arnott et al ., ) show that in some locations, strong winds during storms actually lead to significant dune growth, even when dry‐beach fetch is significantly reduced. For example, the strong extratropical event in February 2016 triggered one of the largest growth intervals at Nags Head (Figure e).…”
Section: Discussionmentioning
confidence: 99%
“…Storms are most often considered erosional events to dunes, but results here and from other studies (e.g. Hesp et al ., ; Davidson‐Arnott et al ., ) show that in some locations, strong winds during storms actually lead to significant dune growth, even when dry‐beach fetch is significantly reduced. For example, the strong extratropical event in February 2016 triggered one of the largest growth intervals at Nags Head (Figure e).…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 displays the drift potentials only (i.e., DP and RDP), and most prograded sites have high sediment transport potential (>18 v.u). This indicates that strong onshore (and alongshore) winds are important processes that transport sediment supplied to the beachface, into the foredunes, and contribute to dune building [30].…”
Section: Accreting Shorelinesmentioning
confidence: 99%
“…On a global scale, there are only a handful of studies that have looked at regional scale foredune evolution, especially over the intermediate (or engineering) timescale, which include the following: Areas of the USA, Canada, The Netherlands, and Italy [8,23,[27][28][29][30]. In NSW, there have been several localised investigations that have looked at foredune (or shoreline) evolution at this timescale, for example, at Bengello Beach (found in the far-south of NSW), a 45-year beach-foredune monitoring program is still being conducted, which has documented how those foredunes have eroded as a , which are strongly controlled by the degree of vegetation cover.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling suggests that the height of purely aeolian foredunes could reflect a steady state condition associated with the local sediment supply regime and the presence/absence of stabilizing vegetation (Vinent & Moore, ). More recently, it has been shown that dune height is primarily a function of sediment supply, whereby vertical growth rate responds strictly to the size of the ridge (Davidson‐Arnott et al, ). For example, under constant input, the rate of elevation gain decreases for progressively larger ridges but never results in a steady state, allowing ridges to continue growing until stabilized inland of the active beach.…”
Section: Background: Development Of Beach and Foredune‐ridge Systemsmentioning
confidence: 99%